LEVEL OF FUNCTIONING OF PATIENTS WITH SEVERE MENTAL ILLNESS BEFORE IMPLEMENTATION OF MULTIDISCIPLINARY COMMUNITY OF MENTAL HEALTH TEAMS IN SKOPJE , REPUBLIC OF NORTH MACEDONIA - Isjanovski, Viktor; Naumovska, Andromahi; Bajraktarov, Stojan (Journal of Morphological Sciences, 2023)
The main objective of this study was to determine and compare differences in the level of functionality in 180 patients with SMI in WHODAS 2.0 according their demographic characteristics- gender, marriage, education, and professional arrangement/income before establishing Community Based mental healthcare in Skopje, North Macedonia. Results show that on subscale Life activities and Participation selected patients are with lower level of functionality. Results for lower level of functionality are obtained on the subscales Cognition and Mobility, and mild level of disability are obtained on the subscales Getting along and Self-care. The general level of functioning of all examined participants is on moderate level of dysfunctionality.   Key words:  mental health, demographic characteristics, severe mental illnesses   https://doi.org/10.55302/JMS2361031i